2005
DOI: 10.1002/cpa.20110
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of vortex sheets

Abstract: We consider the motion of the interface separating two domains of the same fluid that moves with different velocities along the tangential direction of the interface. The evolution of the interface (the vortex sheet) is governed by the Birkhoff-Rott (BR) equations. We consider the question of the weakest possible assumptions such that the Birkhoff-Rott equation makes sense. This leads us to introduce chord-arc curves to this problem. We present three results. The first can be stated as the following: Assume th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 43 publications
(91 reference statements)
4
69
0
3
Order By: Relevance
“…The Kelvin-Helmholtz problem exhibits also some basic similar instabilities, but it is in some sense simpler. This is explained at the end of section 7, where it is also shown that some recent results of [44] , [71] and [72], on the regularity of the vortex sheet (interface), do contribute to the understanding of the instabilities of the original problem.…”
Section: On the Other Hand One Should Observe That The Above Argumenmentioning
confidence: 86%
See 1 more Smart Citation
“…The Kelvin-Helmholtz problem exhibits also some basic similar instabilities, but it is in some sense simpler. This is explained at the end of section 7, where it is also shown that some recent results of [44] , [71] and [72], on the regularity of the vortex sheet (interface), do contribute to the understanding of the instabilities of the original problem.…”
Section: On the Other Hand One Should Observe That The Above Argumenmentioning
confidence: 86%
“…Up to now, the best (to the best of our knowledge) known result is due to S. Wu [71] [72]. The hypothesis C α loc (R t ; C 1+β loc (R λ )) is replaced by H 1 loc (R t × R λ ) .…”
Section: Analyticity and Pathologic Behavior After The Break Down Of mentioning
confidence: 99%
“…The jump discontinuity in the tangential component of velocity across the material interface, which appears in the two-phase Euler model, is responsible for the ill-posedness of this system of PDE when surface tension effects are ignored (see [9] and [20]). On the other hand, in the presence of surface tension, the two-phase system is well-posed.…”
mentioning
confidence: 99%
“…[133,20,36], and it is known to be ill posed if one goes beyond the analytic framework [36,21]. As for the relation between the analyticity and the regularity of the solution to the Birkhoff-Rott equations, see also [88,146] and references therein. The Navier-Stokes equations in R n with vortex sheets as initial data are locally well-posed when n = 3 and globally well-posed when n = 2 since the velocity field in this class has enough local regularity to construct a unique solution.…”
Section: )mentioning
confidence: 99%